Experiences of physical activity and exercise in individuals with systemic sclerosis: A qualitative study. (6th February 2020) - Pettersson, Henrik; Nordin, Annica; Svenungsson, Elisabet; Alexanderson, Helene; Boström, Carina
Abstract: Introduction: Exercise is emerging as an important part of the treatment in systemic sclerosis‐patients with no‐mild lung involvement. However, it has not been studied how patients experience physical activity and exercises. We thus explored and described experiences of physical activity/exercises in systemic sclerosis‐individuals. Method: Sixteen systemic sclerosis‐patients were purposefully recruited to represent variation in gender, age, and lung disease. Semi‐structured individual interviews were performed, transcribed and analyzed with qualitative content analysis. Results: Three themes (categories) emerged: 1) Essential for life and health (An effective treatment, Reduces fear of deterioration, and Feeling healthy and satisfied with oneself); 2) Disease‐related hinders and other barriers (Disease consequences, Risk of worsening, and Non‐disease related barriers); and 3) Self‐care and/or support (Self‐confidence in physical activity/exercise, and, Education and support from healthcare and other). Conclusions: Physical activity/exercises were experienced as essential for life and health and as an effective treatment. It reduced fear of deterioration and made the participants feel healthy and satisfied with oneself. However, participants also experienced disease‐related barriers like shortness of breath and pain, and they expressed a risk of worsening. Participants felt confidence in their physical activity/exercises and expressed that education and support from healthcare could be facilitating. Our findings add new knowledge about how systemic sclerosis‐patients perceive physical activity/exercise and can contribute to the development of patient education and PA/exercise programs.